Influence of Complete Denture Use on Respiratory Capacity: A Systematic Review - Neves, Bruna R; Leão, Rafaella S; da Silva, Andressa S Carneiro; Júnior, Joel F Santiago; Vasconcelos, Belmiro C Do Egito; Pellizzer, Eduardo P [UNESP]; Moraes, Sandra L Dantas (Jaypee Brothers Medical Publishing, 2021)
Aim and objective: This study aimed to determine whether the use of complete dentures has an influence on the respiratory capacity, assessed by the spirometry examination. Materials and methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis and registered in the International Prospective Register of Systematic Reviews (CRD42021255224). The PICO question (population/exposure/ comparison/outcome) was “Does the use of complete dentures influence the respiratory capacity of a toothless subject?” A search strategy was adapted for the PubMed/MEDLINE, The Cochrane Library, OpenGrey, Lilacs, Scopus, and Embase databases. Inclusion criteria were prospective and retrospective studies. The new castle ottawa (NOS) scale and the Methodological Index for Non-randomized studies were selected to assess the quality of the included studies. Results: Four studies were selected, totalizing the evaluation of 242 participants, aged ranging from 40 to 73 years old. Two studies concluded that the use of complete dentures can negatively affect the respiratory capacity. One study stated that it did not interfere regardless of its use during spirometric measurements, and the other reported that dental prosthesis was required in cases of evaluation of the extrathoracic airways. Conclusion: The use of complete dentures did not represent relevant changes from the reference values for pulmonary function in the spirometry test. Considering the results of this review, it is not yet possible to establish a clinical protocol for the use of complete dentures during the test. Clinical significance: Oral rehabilitation with conventional complete dentures is widely used for the treatment of edentulism, especially in elderly patients. In addition, with aging, many complex changes in immunity and respiratory function contribute to the increase in the development of lung diseases. Therefore, it is important to establish a guidance regarding the use or not of the removable dental prostheses in the respiratory capacity test through spirometry examination.
Keywords: Airways; Denture; Respiratory function tests; Spirometry